Investigation of shear bond strength of different adhesive agents to demineralized enamel with or without resin ınfiltration - Rabia Bilgic; Merve Iscan Yapar; Neslihan Celik; Nilgun Akgul (Wolters Kluwer Medknow Publications, 2023)
Objectives: This study aimed to investigate the bond strength of adhesive agents to enamel surfaces with and without resin infiltration. Materials and Methods: The crowns and roots of 198 human incisors were separated from each other and placed in an acrylic mold. The teeth were ground until the guide grooves created with the slotted bur disappeared. Then, it was thrown into the demineralization solution and artificial caries lesions were created. Teeth were randomly divided into two main groups, and each main group was divided into five subgroups. And also the control group was determined. The materials and composite were applied to demineralized enamel. For the shear bond analysis, a universal testing machine was used. Statistical analysis of the data was evaluated by one-way ANOVA test and independent t-test. Results: The result showed that there was no statistical difference between no resin infiltrant adhesive bonding agent groups (P < 0.05) and no difference between resin-treated groups and untreated groups of each bonding agent (P < 0.05). Furthermore, there is no difference between resin infiltrant pretreated adhesive bonding agent groups (P < 0.05). Conclusion: The use of different adhesive systems during restorative procedures after resin infiltration did not affect the shear bond strength.